2012
DOI: 10.1080/14786435.2012.657704
|View full text |Cite
|
Sign up to set email alerts
|

Dislocation emission from a crack under mixed mode loading studied by molecular statics

Abstract: International audienceThe dislocation emission surface in (k(I), k(II), k(III)) space is calculated by means of atomistic simulations for the {111}< 110 > crack in Al. For each relevant combination of loading mode, the precise nature of the dislocations and of the emission process are determined. When appropriate, the analytic formulas proposed by Rice are used by calculating the unstable stacking energy including the effect of the mixed mode loading. Quantitative agreement with the full atomistic calculation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 17 publications
1
11
0
Order By: Relevance
“…On the contrary, it was found that at high H concentrations, the stacking would reconstruct and that it would prevent sliding [19]. An additional motivation for the present study, that will be detailed in a forthcoming paper [20], is the evaluation of the effect of sub-surface hydrogen on, in plane, Shockley partial emission at a crack tip loaded in mixed mode I plus II [21]. In this crack-dislocation configuration, the stress intensity factor is simply related to the lowest local maximum of the GSF (the unstable stacking energy g us ), by the relation: k IIe (k I ) = 2mg us (Du z )/(1 − n) .…”
Section: Introductionmentioning
confidence: 86%
See 1 more Smart Citation
“…On the contrary, it was found that at high H concentrations, the stacking would reconstruct and that it would prevent sliding [19]. An additional motivation for the present study, that will be detailed in a forthcoming paper [20], is the evaluation of the effect of sub-surface hydrogen on, in plane, Shockley partial emission at a crack tip loaded in mixed mode I plus II [21]. In this crack-dislocation configuration, the stress intensity factor is simply related to the lowest local maximum of the GSF (the unstable stacking energy g us ), by the relation: k IIe (k I ) = 2mg us (Du z )/(1 − n) .…”
Section: Introductionmentioning
confidence: 86%
“…The corresponding rigid shear is (Du y = b = 1/6 112 ), where b is the Burgers vector of a Shockley partial (Figure 1). As mentioned in the introduction, the GSF is sensitive to transverse stresses which can be high, for example when considering dislocation emission at crack tips [21,23]. This is taken into account by introducing a displacement Du z normal to the glide plane (the z-direction is along [111]).…”
Section: Methods and Computational Setupmentioning
confidence: 99%
“…where μ and ν are the shear modulus and Poisson ratio of the material. Mode I can be taken into account [25,26] provided the proper transverse opening Du z is included in the calculation of g us . Furthermore, including H in the GSF increases the complexity of the calculation because the neighbourhood of the H atom needs to be relaxed, while the GSF is calculated by rigidly sliding two crystal blocks one on top of the other.…”
Section: Simulation and Modelling Detailsmentioning
confidence: 99%
“…A small mode I is superimposed. k IIe (k I , C H ) values are extracted from the stress maps calculated at the atomic scale by a fit to the elastic solutions [26]. They are used as references.…”
Section: Simulation and Modelling Detailsmentioning
confidence: 99%
“…Evidently, a comprehensive understanding of these processes must involve some degree of atomistic modeling (for example, Refs. [22][23][24] yielded important results pertaining to embryonic dislocation loop emission and crack blunting), last but not least to reconcile continuum models with results of atomistic modeling. Nevertheless, atomistic modeling necessitates an underlying interatomic potential that reproduces the necessary material parameters, dislocation cores, fracture properties, etc., accurately.…”
Section: Introductionmentioning
confidence: 97%